Studies on seminal attributes of Patanwadi rams during breeding and non-breeding seasons - NEMA, S P; KAVANI, F S; GAJBHIYE, P U (The Indian Journal of Animal Reproduction, 2023)
Semen ejaculates (90) collected in artificial vagina from 5 mature Patanwadi rams covering breeding and non-breeding seasons (one year) were evaluated for the biophysical attributes. The overall means of variou; seminal attributes observed were: ejaculate volume 0.91±0.11 ml, mass activityJ.80±0. 9, pH 6.97±0.02, sperm concentration 2730.44±50.50 million/ml, live sperm count 88.49±0.54 %, morphologieally abnormal sperms 5.93±0.12 % and abnormal acrosome score 4.57±0.13 %. ·Variation between rams was highly significant (P < 0.01) for volume and pH and significant (P < 0.05) for all other attributes. The effect of season and ram x season interaction was however, non-significant for all the attributes, except mass activity, which was higher (P < 0.05) during non-breeding season (3.93±0.14 vs. 3.67±0.12). The ejaculate volume had significant negative correlatio• with mass activity (-0.226) and positive correlation with abnormal sperm% (+0.211). The mass motility was significantly correlated with sperm concentration (+0.619) and live sperm% (+0.568) and negatively with pH (- 0.588). Seminal pH had significant negative correlation with sperm concentration (-0.882) and abnormal acrosome score (-0.229). These findings suggested that Patanwadi rams donate good quality semen throughout the year that is suitable for use in artificial breeding programme.